White paper on business of 6G - Yrjölä, Seppo; Ahokangas, Petri; Matinmikko-Blue, Marja (6G Research Visions, ISSN 2669-963X, 2020)
6G vision and the industry consensus of underlying technology enablers have come a long way and will shape the new access, networking, and service domains in future mobile communications. These novel features promise countless opportunities for service innovation and business efficiencies, creating an unprecedented impact on multiple vertical sectors. 6G will connect worlds in novel and innovative ways - the physical and digital worlds will be deeply intertwined in real time, human biological systems will be seamlessly coupled, and at the same time, there will be a new human sensory and cognitive dimension across the scenarios of the 6G experience. Key technology-enabling themes to be explored will include the pervasive leverage of machine learning and artificial intelligence across architectural domains to flexibly define the air interface, as well as service management and orchestration in the 6G "network of networks" topology and platform ecosystem. Terahertz (THz) research is one of the prominent topics, utilizing spectral bands of above 100 GHz for both communications and sensing purposes, thereby enabling connectivity data speeds in the Terabit/s range. We foresee millions of sub-networks and devices becoming the network in conjunction with extreme performance attributes in terms of both sub-millisecond latency, high reliability and time-sensitive determinism, and advanced ways to assure security, privacy, and trust.In line with 6G vision and technology enablers, developing products, services, and vertical applications for the future digitized society in the 6G era requires a multidisciplinary approach and a redefinition of how we create, deliver, and consume network resources, data, and services for both communications and sensing purposes. This development will change and disrupt the traditional business models and ecosystem roles of digital service providers, as well as open the market for key stakeholders in the 6G era like digital service operators, cloud operators, and resource brokers. Furthermore, sustainable development is a highly complex area that will call for major changes in industrialized society in the long run. This white paper discusses the unprecedented opportunities to enable and empower multiple stakeholders to more actively participate in the future 6G ecosystem via novel sustainable open ecosystemic business models with flexible integration of long tail services with tailored performance attributes. This research adopts a qualitative scenario planning method, portraying three scenario themes resulting in a total of 12 scenarios for the futures of the 6G business. We present both optimistic and pessimistic scenarios, and assess their probability, plausibility, and preferability. By focusing on key trends, their interactions, and irreducible uncertainties, scenario building generates perspectives for the futures within which alternative 6G business strategies have been developed and assessed for a traditional incumbent mobile network operator, and a novel 6G digital service provider stemming from redefined sustainable economics. Value capture in the 6G era requires an understanding of the dynamics of platforms and ecosystems. The results indicate that to reach some of the preferred futures, we should attend to the privacy and security issues related to business and regulation needs: public/governmental, corporate, community, and user perspectives on and aims of governance; ecosystem configuration related to users, decentralized business models, and platforms; user empowerment; and the role of service location-specificity.
Keywords: Sustainability; Ecosystem; 6G; anticipatory action learning; business model; scenario planning